Analysis Of School Field Introduction Difficulties For Students In Applicing Teaching Skills During Pandemic - Dian Utami, M.Pd.; Yarmaidi Yarmaidi; Edy haryono (Journal Learning Geography, 2022)
The purpose of this study was to examine the difficulties faced and the efforts that could use by PLP students in the Department of Geography Education Lampung University in applying teaching skills in schools during the Pandemic. The research method used is a qualitative descriptive approach. Collecting data using questionnaires, interviews, and documentation techniques. Data analysis was carried out using the Miles and Huberman model. The results of the research are (1) the difficulties experienced by students, namely the skills to open lessons, the skills to explain, the skills to provide reinforcement and the skills to carry out variations; (2) the efforts made in the form of holding a face-to-face meeting once and learning how to teach well through video media.